2023
DOI: 10.1007/s00167-023-07402-2
|View full text |Cite
|
Sign up to set email alerts
|

Lower donor site morbidity with hamstring and quadriceps tendon autograft compared with bone-patellar tendon-bone autograft after anterior cruciate ligament reconstruction: a systematic review and network meta-analysis of randomized controlled trials

Abstract: PurposeTo perform a meta‐analysis of RCTs evaluating donor site morbidity after bone–patellar tendon–bone (BTB), hamstring tendon (HT) and quadriceps tendon (QT) autograft harvest for anterior cruciate ligament reconstruction (ACLR). MethodsPubMed, OVID/Medline and Cochrane databases were queried in July 2022. All level one articles reporting the frequency of specific donor‐site morbidity were included. Frequentist model network meta‐analyses with P‐scores were conducted to compare the prevalence of donor‐site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 48 publications
(92 reference statements)
1
7
0
Order By: Relevance
“…Hamstring tendon autograft was the most frequent autograft choice in our cohort (91%), followed by patellar tendon graft in 8.6%. The high use of hamstring tendon autograft is consistent with the findings from other European registries, such as the Scandanavian registries [24][25][26][27][33][34][35]. However, BTB is a more popular autograft choice in studies from the United States [36,37].…”
Section: Vte Risk Groupssupporting
confidence: 83%
“…Hamstring tendon autograft was the most frequent autograft choice in our cohort (91%), followed by patellar tendon graft in 8.6%. The high use of hamstring tendon autograft is consistent with the findings from other European registries, such as the Scandanavian registries [24][25][26][27][33][34][35]. However, BTB is a more popular autograft choice in studies from the United States [36,37].…”
Section: Vte Risk Groupssupporting
confidence: 83%
“…52 When compared to other graft options, the QT graft has benefits such as lower morbidity at the donor site (defined as anterior knee pain, difficulty or inability to kneel or both) when compared to the patellar tendon autograft. 53 In a cohort study, ACL reconstruction using a QT graft showed a lower rate of rerupture when compared to autologous flexor graft. 54 In a recent study with 6,652 ACL reconstructions, cases using QT graft had a lower rate of septic arthritis when compared to cases using flexor grafts, patellar tendon grafts or allografts.…”
Section: Autologous Quadricipital Tendon Graftmentioning
confidence: 99%
“…The median number of studies included was 15 (IQR = 8.6-21.4) and the median number of total patients included was 1398 (IQR = 771.5-2024.5). Studies were published in 21 different journals, with the most common journals of publication being: The Journal of Arthroscopic and Related Surgery (nine studies; 18%) [4,5,10,11,13,25,32,54,60], The American Journal of Sports Medicine (seven studies; 14%) [6,16,22,23,48,67,69] and Knee Surgery, Sports Traumatology, Arthroscopy (six studies; 12%) [26,35,40,41,49,72]. The most commonly investigated comparison of autografts in included studies was HT versus BPTB (35/50, 70%), followed by QT versus HT versus BPTB (9/50, 18%), QT versus HT (3/ 50, 6%) and QT versus BPTB (1/50, 2%).…”
Section: Study Characteristicsmentioning
confidence: 99%